Telehealth in outpatient care for children and adolescents with chronic conditions during the COVID-19 pandemic: A scoping review protocol. - Larissa Karoline Dias da Silva Casemiro; Luís Carlos Lopes-Júnior; Fabrine Aguilar Jardim; Mariane Caetano Sulino; Regina Aparecida Garcia de Lima (PLoS ONE)
Introduction Outpatient care for children and adolescents with chronic conditions needs to be continuous and programmed, encompassing comprehensive care, with periodically scheduled consultations, exams, and procedures, to promote quality of life and reduce mortality. In the context of the new coronavirus pandemic, however, outpatient care for children and adolescents with chronic conditions, in person, was hampered in favor of social isolation, a necessary sanitary measure to reduce and prevent the spread of Coronavirus Disease 2019. In response to this need, studies suggest telehealth in pediatrics as a fertile and expanding field especially in times of pandemics. Here, we aimed to map the evidence related to telehealth in outpatient care for children and adolescents with chronic conditions during the COVID-19 pandemic, to identify which strategies were implemented and their impacts on the continuity of care. Methods A scoping review protocol is reported and guided by the Scoping Reviews Manual of the Joanna Briggs Institute. The search for evidence will cover the following databases: MEDLINE/PubMed, Cochrane Libary; Embase; Web of Science; Scopus; Cinahl and PsycINFO, plus additional sources, such as The British Library, Google Scholar, and Preprints [medRXiv]. No date or language restrictions will be employed in this scoping review. Two independent researchers will conduct the search strategy, study selection, data charting, and data synthesis. Results The findings will be presented through tables, charts, narrative summaries, and assessed based on the type of data charted as well as outcomes. Additionally, the meaning of these findings will be considered as they relate to the guiding question, the characterization and measurement of the impact of different telehealth modalities used in outpatient care for children and adolescents with chronic conditions during the COVID-19 pandemic, and the implications for practice and further research. Discussion To the best of our knowledge, this will be the first scoping review to look specifically at the telehealth modalities to be used in outpatient care for children and adolescents with chronic conditions during the COVID-19 pandemic. We expect that our results will be of interest to practitioners as well as researchers concerned with this particular emerging issue in the pandemic context. Also, the plans for the dissemination of this study comprise peer-reviewed publication and conference presentations. Trial registration Open Science Framework Registration: osf.io/5pqgu.